Toxicological Evaluation of Some Organophosphorus Compounds against Larvae of Culex quinquefasdatus in Bikaner District, Rajasthan - Bansal, S K; Singh, Karam V (Annals of Arid Zone, 2016)
Effects of six organophosphorus compounds, viz., malathion, fenitrothion, fenthion, dichlorvos, temephos and chlorpyrifos were evaluated on larvae of Culex quinquefasciatus, the vector of lymphatic filariasis. Different diagnostic concentrations supplied by WHO were used and per cent mortalities determined. LCso values, as determined by probit analysis, were 1.273, 0.109], 0.0947, 0.0458, 0.0076 and 0.0038 mg L-1, respectively. Chlorpyrifos and temephos were the most toxic where ]00% mortality was observed while fenitrothion, fenthion and dichlorvos were found in between these two extremes. Regression coefficient (slope), fiducial limits to LCso and LC95 and heterogeneity of the response (x2 ) were calculated for each insecticide.'